Speech-Language Therapist Staffing for the Rehabilitation of Adult and Paediatric In/Outpatients in Chilean Public Hospitals - Felipe Gonzalo Rosales Lillo; Patricia Castro Abarca; Antonia Villalón Barrionuevo; Haranni Antonella Aguilera Soto; Teresita Bravo Andrade (Revista de Investigación e Innovación en Ciencias de la Salud, 2025)
Introduction. Speech and language therapists are key in health teams; health institutions must have enough staff for quality care.